Investigation on the occurrence of positive cloud to ground (+CG) lightning in UMP Pekan - Chan, Hwee Geem; Amir Izzani, Mohamed (Elsevier Ltd, 2018)
This paper is going to ﬁnd the direction of +CG lightning and its relationship with monsoon season in Malaysia by using data obtained from Malaysia Meteorological Department (MMD) for 2015. Analysis from this study found that a high numbers of lightning occur during dry season compares to rainy season. This is contradicted with general perception in Malaysia where lightning only occurs during rainy day. It is also understood that +CG lightning makes up approximately 20% of total lightning and the rest is −CG lightning events. The oc-currence of +CG lightning during day and night will be discussed. From this, the direction where most +CG lightning occurs will be determined and used as a guide in order to observe TLEs afterward.